A new health literacy scale for staff in preschool childcare institution: development and preliminary validation - Xinqi Zhuang; Yitong Jia; Tianxin Cui; Ge Meng; Jianzhong Zhang; Linxia He; Yin-Ping Zhang (BMC Public Health)
Abstract Background The health literacy of staff in preschool childcare institution is an important issue to consider in providing healthcare for children aged 3–6 years, which could contribute to reducing incidence of diseases and accidental injuries as well as maintaining children’s good health. Seldom instruments have been designed to measure health literacy across this group. This research aims to develop a health literacy scale for staff in preschool childcare institutions and validate its psychometric properties. Methods The scale was developed through four phases. In Phase 1, an item pool was developed mainly based on literature review and kindergarten work; In Phase 2, the initial items were reviewed by fifteen experts and content validity analysis was conducted; In Phase 3, a pilot study was conducted involving 30 kindergarten staff, which aimed to further modify the scale; In Phase 4, a psychometric validation study involving 466 kindergarten staff was conducted through a cross-sectional survey in May 2023. Item analysis was performed through critical ration, correlation analysis, and Cronbach’s alpha if item deleted. Construct validity was performed through exploratory (n = 190) and confirmatory factor analyses (n = 276). Convergent and discriminant validity were evaluated. Reliability was evaluated through internal consistency, split-half reliability, and test-retest reliability. Results The final Health Literacy Scale consisted of 28 items, including dimensions of Basic Health Knowledge (11 items), Functional Health Literacy Skills (3 items), Communicative Health Literacy (5 items), and Critical Health Literacy (9 items). Principal component analysis revealed a four-factor structure that explained 80.092% of the total variance. The goodness-of-fit indices signified an adequate model fit (χ2/df = 2.093, RMSEA = 0.063, RMR = 0.031, GFI = 0.852, CFI = 0.958, NFI = 0.923, IFI = 0.958, TLI = 0.953, PCFI = 0.844). Cronbach’s alpha showed a good internal consistency reaching a value of 0.921. The split-half reliability was 0.805, and the test-retest reliability was good with an intraclass correlation coefficient of 0.885 (P < 0.001). Conclusions The Health Literacy Scale developed in this research focuses on health literacy issues related to children aged 3–6 years. The scale is demonstrated to be valid and reliable for assessing the health literacy of staff in preschool childcare institutions. It could potentially be used as an effective instrument for targeted development of health literacy intervention.